Ischemic Heart Disease. Blood Coagulation System in Tension Angina Pectoris - Karabayeva Feruza Alijon kizi; Yuldasheva Nodira Ergashevna (Zien Journals, 2024)
The purpose of the study was to evaluate the dynamics of changes in the parameters of the hemostatic system and the volume of blood loss in patients with coronary heart disease (CHD) and arterial hypertension (AH) who underwent coronary artery bypass grafting depending on their sensitivity to aspirin. It has been shown that the volume of blood loss in the intra- and postoperative period of coronary artery bypass surgery (CABG), the dynamics of coagulogram and thromboelastogram parameters do not depend on the low sensitivity of patients to aspirin
Keywords: coronary artery bypass grafting; blood loss; aspirin resistance; aspirin